Cognitive phenomenology - Bayne, Tim.; Montague, Michelle (Oxford : Oxford University Press, 2011)
The central concern of the cognitive phenomenology debate is whether there is a distinctive 'cognitive phenomenology,' that is, a kind of phenomenology that has cognitive or conceptual character in some sense that needs to be precisely determined. This volume addresses the question of whether conscious thought has cognitive phenomenology.
Includes bibliographical references and index.
Also issued in print format.
Description based on online resource; title from PDF title page (viewed on Jan. 20, 2012).
Keywords: Phenomenology; Philosophy of mind; Cognitive science